2017
DOI: 10.1111/efp.12390
|View full text |Cite
|
Sign up to set email alerts
|

Screening for host responses in Acacia to a canker and wilt pathogen, Ceratocystis manginecans

Abstract: Summary 13In Vietnam, the productivity of Acacia hybrid (Acacia mangium x A. auriculiformis) 14 plantations is being threatened by an aggressive canker pathogen, Ceratocystis manginecans 15 and selection for tolerance is the main control strategy. A pot trial was established in Binh 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Thus, it can be inferred that Q. infectoria upregulated the expression of phenol‐ and flavonoid‐associated genes, enhancing their accumulation and biological activity, while this defense mechanism seems poorly developed in Q. libani . Trang et al () observed higher concentrations of tannins in the more tolerant Acacia genotypes when plants were attacked by pathogens, so tannins can also be regarded as an indicator of tolerance to pathogens. Interestingly, tannin content in leaves of Q. libani dramatically increased when their seedlings experienced charcoal disease under water deficit.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it can be inferred that Q. infectoria upregulated the expression of phenol‐ and flavonoid‐associated genes, enhancing their accumulation and biological activity, while this defense mechanism seems poorly developed in Q. libani . Trang et al () observed higher concentrations of tannins in the more tolerant Acacia genotypes when plants were attacked by pathogens, so tannins can also be regarded as an indicator of tolerance to pathogens. Interestingly, tannin content in leaves of Q. libani dramatically increased when their seedlings experienced charcoal disease under water deficit.…”
Section: Discussionmentioning
confidence: 99%
“…and its original host, Eucalyptus spp. in China, Indonesia, South Africa, Thailand, Uruguay ( Harrington et al, 2014 ), Zimbabwe ( Jimu et al, 2015 ) and Vietnam ( Trang et al, 2018 ). The member of this Eucalyptus population of C. fimbriata cause the wilt epidemic on kiwifruit in Brazil ( Ferreira et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, no strains of A. mangium resistant to Ceratocystis have been identified, though there is evidence of some variation in disease tolerance (Brawner 2015). Acacia auriculiformis shows higher levels of tolerance to C. manginecans, and this tolerance may also be expressed in A. mangium × A. auriculiformis hybrids (Trang et al 2018).…”
Section: Genetic Control Of Ceratocystismentioning
confidence: 99%